2014
DOI: 10.1177/0284185113506190
|View full text |Cite
|
Sign up to set email alerts
|

A study of clinical complications and risk factors in 1001 native and transplant kidney biopsies in Sweden

Abstract: The present findings motivate greater attention being paid to the risk of major side-effects after right-side biopsies from women's kidneys, as well as after biopsies from younger patients and patients with lower BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 22 publications
4
44
1
Order By: Relevance
“…In contrast to some studies, our findings showed that amyloidosis was the most common diagnosis, followed by membranous nephropathy in patients over 65 years [12,[14][15][16][17]. In our study, overall complication rate of renal biopsies was 4.08 %, which was lower than the complication rate of younger age and even pediatric age group patients of other studies [18,19].…”
Section: Discussioncontrasting
confidence: 89%
“…In contrast to some studies, our findings showed that amyloidosis was the most common diagnosis, followed by membranous nephropathy in patients over 65 years [12,[14][15][16][17]. In our study, overall complication rate of renal biopsies was 4.08 %, which was lower than the complication rate of younger age and even pediatric age group patients of other studies [18,19].…”
Section: Discussioncontrasting
confidence: 89%
“…This single-center cohort is the largest known to be published (>2500 patients), and we demonstrated a similar rate of major complications compared with prior published reports (0-4%) (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Several very clinically important conclusions were drawn relating to renal transplant biopsy complications.…”
Section: Discussionsupporting
confidence: 80%
“…Interventional embolization and coiling of the feeder vessel or the aneurysm itself are rarely required. Malignant conversion with total or partial organ loss, is rare [25,66,[70][71][72][73][74][75][76][77][78][79][80][81].…”
Section: Hemorrhagementioning
confidence: 99%
“…For advanced guidance, bleeding risk predictors are summarized in Table II. [72] 10. Lower BMI [72] 11.…”
Section: Bleeding Risk Modification and Risk Reduction Techniquesmentioning
confidence: 99%
See 1 more Smart Citation